Dinâmica sazonal de nutrientes nos solos em diferentes fitofisionomias vegetais no Norte do Pantanal Mato-Grossense - Nassarden, Danielle Christine Stenner (2016)
The Pantanal undergoes frequent fluctuations of the flood levels, these in turn, are caused by rainfall variation and changes in the dynamics of sediments over the time. The flood pulse changes the chemical and physical properties of the soil, changing the concentration of nutrients. This regime of flood corroborates to the development of some species of invasive and monodominant vegetation. In this sense, the objective of this study was to understand the dynamics of soil nutrients in different phytophysiognomies, under different hydrological conditions in Northern Pantanal of Mato Grosso. The study was performed at Baía das Pedras Park in the Ecological Resort SESC Pantanal in Poconé / MT. The samples were collected in the soil of 03 phytophysiognomies named Cambará, Flooded Field and Pombeiral, and at each location were removed 03 samples of indeformed soil. The gathering was held in three distinct hydrological periods, been them before the flood (December / 2013), after the flood (July / 2014) and at the dry (October / 2014). There was an increase of organic matter after the flood at Cambara and Pombeiral soils. There was differences in the concentration of soil nutrients according to the type of vegetation and with the hydrological period. There was a change in the pH of the soil after the flood. The concentration of H + interfered in soil acidity, and thus replacing essential elements such as Ca + Mg.